La competencia digital para fortalecer del desarrollo profesional docente (Memorias Sifored - Encuentros Educación UAN, 2023)
Digital competence to strengthen teachers' professional development is a matter of great importance that requires cognitive and emotional work and exercise at the personal and collective level. The objective of the research is to evaluate a proposal for teacher training in digital competencies that promotes the strengthening of professional development. The research is being carried out based on a methodology with a mixed descriptive cross-sectional design and is developed with teachers of basic secondary education. This methodology is structured in phases: in phase 1, the systematic literature review and the problem statement were carried out, which includes the low levels of digital competencies by teachers in pedagogical practices; in phase 2, the categorization of previous digital competencies was made with an empirical analysis; in phase 3, the status of digital competencies in teachers is visualized; and in phase 4, the design and evaluation of the training proposal in digital competencies is made. From the research, we seek to improve the pedagogical performance of teachers and the learning process of students.
Keywords: Digital competency; Teaching professional development; pedagogical practice; basic education